Nutritional interventions in the management of endometriosis - review of the literature - Maja Kotowska; Gabriela Różańska-Smuszkiewicz; Paweł Smuszkiewicz-Różański; Wiktoria Zamirska; Anna Zygmunt; Katarzyna Zięba; Karolina Koszyczarek; Albin Ziemiański (Kazimierz Wielki University, 2024)
Endometriosis, a chronic inflammatory condition, affects approximately 10% of women in their reproductive years, impacting around 176 million individuals globally. Characterized by endometrium-like tissue outside the uterine cavity, it leads to symptoms like chronic pelvic pain, dysmenorrhea, and infertility, severely impairing quality of life. This study aims to investigate the role of nutritional interventions in managing endometriosis, highlighting their potential impact and clinical implications.